The price-link in the German natural gas market: The development of the oil price-link and alternative price mechanisms - Stefan J. Saatmann (Fachhochschule Stralsund, Stralsund Information Management Team (SIMAT), 2013)
This SIMAT Working Paper deals with an intensively discussed topic in the German natural gas economy: The price-link in natural gas contracts. Because of opposite price developments of the energy commodities such as oil, coal or natural gas, the traditionally used oil price-link is facing a reset. Shifting market dynamics in supply and demand of natural gas are the fundamental reason for that and led to intensive debate between the contract partners.
urn:nbn:de:0226-simat05130239
Keywords: L11; L95; L98; 650; competition; gas market; Germany; natural gas; natural gas pricing mechanisms; oil; Energieversorgung; Wettbewerbsanalyse; Marktmechanismus; Erdgas; Erdöl; Erdgasmarkt; Deutschland